Solid oxide fuel cell and manufacturing method thereof
By using ultrafast laser sintering technology to prepare anode, electrolyte, and cathode functional layers layer by layer on a porous metal support, the problems of metal support oxidation and grain coarsening in traditional SOFC preparation are solved, and the rapid preparation of efficient and low-cost metal-supported solid oxide fuel cells is realized.
Patent Information
- Application Number
- CN202511185349.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-08-22
- Publication Date
- 2025-11-28
AI Technical Summary
Traditional SOFC manufacturing processes are prone to oxidation of the metal support, coarsening of Ni grains in the anode, and interdiffusion of elements during high-temperature sintering, resulting in reduced battery performance and lifespan. In addition, the manufacturing process is time-consuming and involves many steps.
Ultrafast laser sintering technology was used to spray an aerosol suspension onto a porous metal support, and the anode, electrolyte and cathode functional layers were prepared layer by layer. The porosity was controlled by adjusting the laser parameters and the solid content of the aerosol to form a multi-scale stacked structure.
This has enabled the efficient fabrication of metal-supported solid oxide fuel cells with high output power, rapid start-stop, and long lifespan, reducing fabrication costs and simplifying the process.
Smart Images

Figure CN121035231A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of additive manufacturing, in particular to a solid oxide fuel cell and a manufacturing method thereof. BACKGROUND
[0002] The core structure of the solid oxide fuel cell is a support body and a functional layer, and the functional layer is divided into an anode layer, an electrolyte layer and a cathode layer. The metal support type has a wide application prospect at present. The porous metal is used as the support body, which can significantly reduce the thickness of the power generation functional layer, the working temperature can be reduced to below 750 DEG C, and the metal support type fuel cell has the advantages of high output power, fast start-stop speed, long cycle life and low cost. The traditional SOFC preparation process mainly includes flow casting and slurry coating methods, which need to be sintered at about 1400 DEG C for multiple times, and the preparation time is long and the process is multiple, which is not suitable for the metal support type fuel cell. Because high-temperature sintering is easy to cause oxidation of the metal support body, anode Ni grain coarsening and element interdiffusion, etc., the performance and service life of the MS-SOFC cell are reduced. SUMMARY
[0003] In order to overcome the above-mentioned deficiencies existing in the prior art, the present application provides a solid oxide fuel cell and a manufacturing method thereof. The solid oxide fuel cell comprises a support body and a functional layer; the material of the functional layer is nickel, cerium oxide, yttrium oxide, zirconium oxide, gadolinium oxide, lanthanum strontium cobalt iron, etc.
[0004] According to the first aspect of the present application, the present application provides a manufacturing method of a solid oxide fuel cell. The method comprises the following steps:
[0005] The metal powder is prepared into a porous metal support body through continuous laser treatment, the anode aerosol suspension is sprayed on the porous metal support body, the first ultrafast laser sintering treatment is carried out, the anode functional layer is obtained, then the electrolyte aerosol is sprayed on the anode functional layer, the second ultrafast laser sintering treatment is carried out, the electrolyte functional layer is obtained, finally, the cathode aerosol suspension is sprayed on the electrolyte functional layer, and the third ultrafast laser sintering treatment is carried out, so as to obtain the solid oxide fuel cell.
[0006] The manufacturing method of the solid oxide fuel cell provided by the present application is an integrated manufacturing method of the solid oxide fuel cell.
[0007] In some embodiments, the thickness of the porous metal support body is 0.5-5mm, and the porosity is 20%-60%.
[0008] In some embodiments, the thickness of the porous metal support body is 0.5-2mm, and the porosity is 30%-50%.
[0009] In some embodiments, the preparation of the porous metal support body comprises the following steps:
[0010] The metal powder is subjected to continuous laser treatment to obtain a porous metal support; the power of the continuous laser treatment is 100-400 W, the scanning speed is 500-2000 mm / s, and the layer thickness of each powder laying in the continuous laser treatment is 20-100 μm; the metal powder is at least one of stainless steel, nickel-based alloy, and cobalt-based alloy.
[0011] In some embodiments, the power of the continuous laser treatment is 150-350 W, the scanning speed is 700-1500 mm / s, and the layer thickness is 20-80 μm.
[0012] In some embodiments, the preparation of the anode aerosol suspension includes the following steps: adding nano-nickel oxide (NiO) and gadolinium-stabilized cerium oxide (GDC) into a solvent and uniformly dispersing to prepare an anode aerosol solution;
[0013] In some embodiments, the mass ratio of the nano-nickel oxide and the gadolinium-stabilized cerium oxide is 3:7-7:3;
[0014] In some embodiments, the solvent is deionized water, anhydrous ethanol, or a mixture of deionized water and anhydrous ethanol;
[0015] In some embodiments, the solid content of the anode aerosol solution is 35wt.%-60wt.%.
[0016] In some embodiments, the preparation of the anode functional layer includes the following steps:
[0017] The anode aerosol suspension is sprayed on the porous metal support by using a large-capacity aerosol nozzle, and a first ultrafast laser sintering treatment is performed to obtain an anode functional layer; the spraying of the anode aerosol suspension and the first ultrafast laser sintering treatment are repeated to make the layer thickness of the anode functional layer be 5-50 μm; the laser power of the first ultrafast laser sintering treatment is 2-20 W, the repetition frequency of the first ultrafast laser sintering treatment is 500-4000 KHz, and the speed of the first ultrafast laser sintering treatment is 100-5000 mm / s; the porosity of the anode functional layer is 20%-60%.
[0018] In some embodiments, the laser power of the first ultrafast laser sintering treatment is 5-15 W, the repetition frequency of the first ultrafast laser sintering treatment is 800-2000 KHz, and the speed of the first ultrafast laser sintering treatment is 800-1500 mm / s.
[0019] In some embodiments, the layer thickness of the anode functional layer is 10-30 μm, and the porosity is 30%-50%.
[0020] In some embodiments, the preparation of the electrolyte aerosol solution includes the following steps:
[0021] Gadolinium-stabilized ceria (GDC) is added to the solvent and dispersed uniformly to prepare an electrolyte aerosol solution;
[0022] In some embodiments, the solvent is deionized water, anhydrous ethanol, or a mixture of deionized water and anhydrous ethanol.
[0023] In some embodiments, the solid content of the electrolyte aerosol solution is 35wt.% to 60wt.%.
[0024] In some embodiments, the preparation of the electrolyte functional layer comprises the following steps:
[0025] The electrolyte aerosol solution is sprayed on the anode functional layer using a large-capacity aerosol nozzle, and a second ultrafast laser sintering treatment is performed to obtain the electrolyte functional layer; the thickness of the electrolyte functional layer is 5 to 30 μm by repeating the above operations of spraying the electrolyte aerosol suspension and the second laser sintering treatment; the laser power of the second laser sintering treatment is 2 to 20 W, the repetition frequency is 100 to 4000 KHz, and the speed is 500 to 5000 mm / s; the porosity of the electrolyte functional layer is <0.3%.
[0026] In some embodiments, the laser power of the second laser sintering treatment is 5 to 15 W, the repetition frequency is 800 to 2000 KHz, and the speed is 800 to 1500 mm / s.
[0027] In some embodiments, the thickness of the electrolyte functional layer is 5 to 15 μm, and the porosity is ≤0.1%.
[0028] In some embodiments, the preparation of the cathode aerosol suspension comprises the following steps:
[0029] Lanthanum strontium cobalt iron (LSCF) is added to the solvent and dispersed uniformly to obtain a cathode aerosol solution;
[0030] In some embodiments, the solvent is deionized water, anhydrous ethanol, or a mixture of deionized water and anhydrous ethanol.
[0031] In some embodiments, the solid content of the cathode aerosol solution is 35wt.% to 60wt.%.
[0032] In some embodiments, the preparation of the cathode functional layer comprises the following steps:
[0033] The cathode aerosol suspension is sprayed on the electrolyte functional layer, and a third ultrafast laser sintering treatment is performed to obtain the cathode functional layer; the thickness of the cathode functional layer is 5 to 50 μm by repeating the above operations of spraying the cathode aerosol suspension and the third ultrafast laser sintering treatment.
[0034] In some embodiments, the third ultrafast laser sintering process has an ultrafast laser power of 2-20 W, a repetition frequency of 100-4000 KHz, and a speed of 500-5000 mm / s.
[0035] In some embodiments, the cathode functional layer has a porosity of 20-60%.
[0036] In some embodiments, the third ultrafast laser sintering process has an ultrafast laser power of 5-15 W, a repetition frequency of 800-2000 KHz, and a speed of 800-1500 mm / s.
[0037] In some embodiments, the cathode functional layer has a layer thickness of 10-30 microns and a porosity of 40-50%.
[0038] According to a second aspect of the present application, the present application provides a solid oxide fuel cell prepared by the manufacturing method described above.
[0039] In some embodiments, the battery prepared by the present application has a power of 0.7-1.5 W / cm 2 at 700℃ when using hydrogen as fuel, and an electrical resistance of less than 0.6 Ω / cm 2 .
[0040] The battery prepared by the present application has a multi-scale laminated structure. The battery as a whole has a centimeter-level structure, the layer thickness of the metal support is millimeter-level, and the thickness of each layer in the functional layer is micron-level. The porosity of the support, anode, and cathode is from nanometer-level to micron-level. Therefore, the battery has a multi-scale or cross-scale laminated structure.
[0041] Compared with the prior art, the present application has the following beneficial effects and advantages:
[0042] (1) The manufacturing method provided by the present application is a novel integrated preparation method of a metal-supported solid oxide fuel cell. By adjusting the ultrafast laser parameters and the solid content of the aerosol, the internal porosity of the functional layer can be controlled, and the anode functional layer, electrolyte functional layer, and cathode functional layer prepared thereby have a multi-scale laminated structure, which is expected to provide technical support for the future large-scale and efficient preparation of metal-supported solid oxide fuel cells.
[0043] (2) The manufacturing method provided by the present application can control the porosity of the functional layer by adjusting the power, repetition frequency, speed, and solid content of the aerosol. Suitable porosity can promote the diffusion speed of the fuel gas and air, thereby affecting the power generation efficiency.
[0044] (3) The manufacturing method provided by the application can obtain a solid oxide fuel cell with an ultra-thin and dense electrolyte functional layer, which can bring the technical effects of small resistance and large power;
[0045] (4) The solid oxide fuel cell provided by the application has the advantages of high output power, fast start-stop speed (start-up time is 15-50 min), long cycle life, few preparation processes, low cost and the like. BRIEF DESCRIPTION OF DRAWINGS
[0046] Figure 1 A structural schematic diagram of a solid oxide fuel cell provided by an embodiment of the application is shown in the figure.
[0047] Figure 2 A schematic diagram of a functional layer in a cell provided by an embodiment of the application is shown in the figure. DETAILED DESCRIPTION
[0048] The application will be further described in detail below in combination with embodiments, but the embodiments of the application are not limited thereto. It should be noted that, if there are processes or parameters not particularly described below, they can be understood or implemented by those skilled in the art according to the prior art.
[0049] Embodiment 1
[0050] A manufacturing method of a solid oxide fuel cell comprises the following steps:
[0051] (1) A stainless steel metal support body powder raw material is subjected to continuous laser treatment to form a porous metal support body; a metal powder is subjected to continuous laser treatment to obtain a porous metal support body; the power of the continuous laser treatment is 150 W, the scanning speed is 1200 mm / s, and the layer thickness of each powder laying in the continuous laser treatment is 20 μm; the porosity of the metal support body is 50%, and the layer thickness is 2 mm;
[0052] (2) Nano nickel oxide (NiO) and gadolinium stabilized cerium oxide (GDC) are added to deionized water and uniformly dispersed to obtain an anode aerosol solution (solid phase content is 35 wt.%), and the mass ratio of the nano nickel oxide (NiO) and the gadolinium stabilized cerium oxide (GDC) is 3:7; the GDC is added to deionized water and uniformly dispersed to configure a 40 wt.% electrolyte aerosol solution; lanthanum strontium cobalt iron (LSCF) is added to deionized water and uniformly dispersed to configure a 35 wt.% cathode aerosol solution;
[0053] (3) The prepared anode aerosol suspension is sprayed onto the surface of the metal support body by using a large-capacity aerosol nozzle;
[0054] (4) Adopting ultrafast laser, laser sintering treatment is carried out on the anode aerosol on the surface of the support body, laser power is 5W, repetition frequency is 1000KHz, and the speed is 800mm / s;
[0055] (5) Repeating step (3) and step (4), the preparation of the anode functional layer is completed, the layer thickness is 30μm, and the porosity is 50%;
[0056] (6) The prepared electrolyte aerosol suspension is sprayed to the surface of the anode by using a large-capacity aerosol nozzle;
[0057] (7) Adopting ultrafast laser, laser sintering treatment is carried out on the electrolyte aerosol on the surface of the anode, laser power is 10W, repetition frequency is 2000KHz, and the speed is 800mm / s;
[0058] (8) Repeating step (6) and step (7), the preparation of the electrolyte functional layer is completed, the thickness of the electrolyte functional layer is 15μm, and the porosity is less than 0.1%;
[0059] (9) The prepared cathode aerosol suspension is sprayed to the surface of the electrolyte functional layer by using a large-capacity aerosol nozzle;
[0060] (10) Adopting ultrafast laser, laser sintering treatment is carried out on the cathode aerosol on the surface of the electrolyte functional layer, laser power is 12W, repetition frequency is 1200KHz, and the speed is 1200mm / s;
[0061] (11) Repeating step (9) and step (10), the preparation of the cathode functional layer is completed, the thickness of the cathode functional layer is 30μm, the porosity is 60%, and a solid oxide fuel cell is obtained;
[0062] The prepared cell (the structure is shown in Figure 1 and Figure 2 , the same below) uses hydrogen as fuel, the power density is 0.75W / cm 2 at 700℃, the resistance is 0.6Ω / cm 2 (Tests are carried out according to the solid oxide fuel cell-cell stack test method in the standards of NB / T 10820-2021 and NB / T 10821-2021, the same below).
[0063] Example 2
[0064] A manufacturing method of a solid oxide fuel cell, comprising the following steps:
[0065] (1) the stainless steel metal support body powder raw material is subjected to continuous laser treatment to form a porous metal support body; the metal powder is subjected to continuous laser treatment to obtain a porous metal support body; the power of the continuous laser treatment is 180 W, the scanning speed is 1500 mm / s, and the layer thickness of each powder laying in the continuous laser treatment is 50 μm; the porosity of the obtained metal support body is 40%, and the layer thickness is 1.5 mm;
[0066] (2) nano nickel oxide (NiO) and gadolinium stabilized cerium oxide (GDC) are added to deionized water to obtain an anode aerosol solution (solid phase content is 40 wt.%), the mass ratio of nano nickel oxide (NiO) and gadolinium stabilized cerium oxide (GDC) is 4:6; GDC is added to deionized water to be uniformly dispersed to prepare a 45 wt.% electrolyte aerosol solution; lanthanum-strontium-cobalt-iron (LSCF) is added to deionized water to be uniformly dispersed to prepare a 40 wt.% cathode aerosol solution;
[0067] (3) the prepared anode aerosol suspension is sprayed onto the surface of the metal support body by using a large-capacity aerosol nozzle;
[0068] (4) the anode aerosol on the surface of the support body is subjected to laser sintering treatment by using an ultrafast laser, the laser power is 10 W, the repetition frequency is 1500 KHz, and the speed is 1000 mm / s;
[0069] (5) steps (3) and (4) are repeated to complete the preparation of the anode functional layer, the layer thickness is 20 μm, and the porosity is 40%;
[0070] (6) the prepared electrolyte aerosol suspension is sprayed onto the surface of the anode by using a large-capacity aerosol nozzle;
[0071] (7) the electrolyte aerosol on the surface of the anode is subjected to laser sintering treatment by using an ultrafast laser, the laser power is 10 W, the repetition frequency is 1500 KHz, and the speed is 800 mm / s;
[0072] (8) steps (6) and (7) are repeated to complete the preparation of the electrolyte functional layer, the thickness of the electrolyte functional layer is 10 μm, and the porosity is less than 0.1%;
[0073] (9) the prepared cathode aerosol suspension is sprayed onto the surface of the electrolyte functional layer by using a large-capacity aerosol nozzle;
[0074] (10) the cathode aerosol on the surface of the electrolyte functional layer is subjected to laser sintering treatment by using an ultrafast laser, the laser power is 10 W, the repetition frequency is 1200 KHz, and the speed is 1000 mm / s;
[0075] (11) repeating step (9) and step (10) to complete the preparation of the cathode functional layer, the thickness of the cathode functional layer is 20 μm, the porosity is 50%, and a solid oxide fuel cell is obtained;
[0076] The prepared battery uses hydrogen as fuel, and has a power of 1.4 W / cm 2 at 700°C, and a resistance of 0.2 Ω / cm 2 .
[0077] Example 3
[0078] A manufacturing method of a solid oxide fuel cell, comprising the following steps:
[0079] (1) forming a porous metal support by continuous laser technology from a stainless steel metal support powder raw material; the metal powder is treated by continuous laser to obtain a porous metal support; the power of the continuous laser treatment is 200 W, the scanning speed is 1000 mm / s, and the layer thickness of each powder laying in the continuous laser treatment is 80 μm; the porosity of the metal support is 30%, and the layer thickness is 1 mm;
[0080] (2) adding nano nickel oxide (NiO) and gadolinium stabilized cerium oxide (GDC) into deionized water to disperse uniformly to obtain an anode aerosol solution (the solid phase content is 45 wt.%), the mass ratio of nano nickel oxide (NiO) and gadolinium stabilized cerium oxide (GDC) is 5:5; GDC is added into deionized water to disperse uniformly to configure a 50 wt.% electrolyte aerosol solution; lanthanum strontium cobalt iron (LSCF) is added into deionized water to disperse uniformly to configure a 45 wt.% cathode aerosol solution;
[0081] (3) using a large-capacity aerosol nozzle to spray the anode aerosol suspension solution onto the surface of the metal support;
[0082] (4) using ultrafast laser to perform laser sintering treatment on the anode aerosol on the surface of the support, the laser power is 15 W, the repetition frequency is 2000 KHz, and the speed is 1000 mm / s;
[0083] (5) repeating step (3) and step (4) to complete the preparation of the anode functional layer, the layer thickness of the anode functional layer is 10 μm, and the porosity is 50%;
[0084] (6) using a large-capacity aerosol nozzle to spray the electrolyte aerosol suspension solution onto the surface of the anode;
[0085] (7) using ultrafast laser to perform laser sintering treatment on the electrolyte aerosol on the surface of the anode, the laser power is 15 W, the repetition frequency is 1500 KHz, and the speed is 1000 mm / s;
[0086] (8) Repeat steps (6) and (7) to complete the preparation of the electrolyte functional layer. The thickness of the electrolyte functional layer is 10 μm and the porosity is <0.1%.
[0087] Step (9) The prepared cathode aerosol suspension is sprayed onto the surface of the electrolyte functional layer using a large-capacity aerosol nozzle.
[0088] Step (10) uses an ultrafast laser to perform laser sintering on the cathode aerosol on the surface of the electrolyte functional layer. The laser power is 15W, the repetition rate is 1200KHz, and the speed is 2000mm / s.
[0089] Step (11) Repeat steps (9) and (10) to complete the preparation of the cathode functional layer. The cathode functional layer has a thickness of 10 μm and a porosity of 60%, thus obtaining a solid oxide fuel cell.
[0090] The prepared battery, using hydrogen as fuel, has a power output of 1.2 W / cm² at 700°C. 2 Resistance 0.35Ω / cm 2 .
[0091] Example 4
[0092] A method for manufacturing a solid oxide fuel cell includes the following steps:
[0093] (1) A porous metal support is formed from nickel-based high-temperature alloy metal support powder raw material by continuous laser technology; the power of the laser treatment is 250W, the speed is 1500mm / s, and the thickness of each powder layer in the continuous laser treatment is 20μm; the thickness of the porous metal support is 0.5mm and the porosity is 30%.
[0094] (2) Add nano-nickel oxide (NiO) and gadolinium-stabilized cerium oxide (GDC) to anhydrous ethanol and disperse them evenly to obtain an anode aerosol solution (solid content of 45 wt.%), with a mass ratio of nano-nickel oxide (NiO) to gadolinium-stabilized cerium oxide (GDC) of 6:4; add GDC to anhydrous ethanol and disperse it evenly to prepare a 50 wt.% electrolyte aerosol solution; add lanthanum strontium cobalt iron (LSCF) to anhydrous ethanol and disperse it evenly to prepare a 45 wt.% cathode aerosol solution;
[0095] (3) The prepared anode aerosol suspension is sprayed onto the surface of the metal support using a large-capacity aerosol nozzle.
[0096] (4) Ultrafast laser is used to laser sinter the anolyte on the surface of the support. The laser power is 15W, the repetition rate is 2000KHz, and the speed is 1000mm / s.
[0097] (5) repeat step (3) and step (4) to complete the preparation of the anode functional layer, the layer thickness is 30 μm, and the porosity is 50%;
[0098] (6) the prepared electrolyte aerosol suspension is sprayed onto the surface of the anode by using a large-capacity aerosol nozzle;
[0099] (7) the electrolyte aerosol on the surface of the anode is subjected to laser sintering treatment by using an ultrafast laser, the laser power is 15 W, the repetition frequency is 1500 KHz, and the speed is 1200 mm / s;
[0100] (8) repeat step (6) and step (7) to complete the preparation of the electrolyte functional layer, the thickness of the electrolyte functional layer is 20 μm, and the porosity is less than 0.1%;
[0101] (9) the prepared cathode aerosol suspension is sprayed onto the surface of the electrolyte functional layer by using a large-capacity aerosol nozzle;
[0102] (10) the cathode aerosol on the surface of the electrolyte functional layer is subjected to laser sintering treatment by using an ultrafast laser, the laser power is 15 W, the repetition frequency is 1200 KHz, and the speed is 1500 mm / s;
[0103] (11) repeat step (9) and step (10) to complete the preparation of the cathode functional layer, the thickness of the cathode functional layer is 30 μm, the porosity is 60%, and a solid oxide fuel cell is obtained;
[0104] The prepared cell has a power of 0.8 W / cm 2 and a resistance of 0.6 Ω / cm 2 when hydrogen is used as fuel at 700 °C.
[0105] Example 5
[0106] A manufacturing method of a solid oxide fuel cell comprises the following steps:
[0107] (1) a nickel-based high-temperature alloy metal support powder raw material is subjected to continuous laser treatment to form a porous metal support; the laser treatment power is 300 W, the speed is 1200 mm / s, and the layer thickness of each powder laying in the continuous laser treatment is 50 μm; the thickness of the porous metal support is 1 mm, and the porosity is 40%;
[0108] (2) The nano nickel oxide (NiO) and gadolinium stabilized ceria (GDC) are added into anhydrous ethanol to be uniformly dispersed to obtain an anode aerosol solution (solid phase content is 50wt.%), the mass ratio of nano nickel oxide (NiO) and gadolinium stabilized ceria (GDC) is 7:3; the GDC is added into anhydrous ethanol to be uniformly dispersed to configure a 55wt.% electrolyte aerosol solution; the lanthanum strontium cobalt iron (LSCF) is added into anhydrous ethanol to be uniformly dispersed to configure a 50wt.% cathode aerosol solution;
[0109] (3) The prepared anode aerosol suspension is sprayed onto the surface of the metal support by using a large-capacity aerosol nozzle;
[0110] (4) The anode aerosol on the surface of the support is subjected to laser sintering treatment by using an ultrafast laser, the laser power is 12W, the repetition frequency is 1500KHz, and the speed is 1200mm / s;
[0111] (5) The steps (3) and (4) are repeated to complete the preparation of the anode functional layer, the layer thickness is 20 microns, and the porosity is 40%;
[0112] (6) The prepared electrolyte aerosol suspension is sprayed onto the surface of the anode by using a large-capacity aerosol nozzle;
[0113] (7) The electrolyte aerosol on the surface of the anode is subjected to laser sintering treatment by using an ultrafast laser, the laser power is 12W, the repetition frequency is 1200KHz, and the speed is 800mm / s;
[0114] (8) The steps (6) and (7) are repeated to complete the preparation of the electrolyte functional layer, the thickness of the electrolyte functional layer is 12μm, and the porosity is less than 0.1%;
[0115] (9) The prepared cathode aerosol suspension is sprayed onto the surface of the electrolyte functional layer by using a large-capacity aerosol nozzle;
[0116] (10) The cathode aerosol on the surface of the electrolyte functional layer is subjected to laser sintering treatment by using an ultrafast laser, the laser power is 12W, the repetition frequency is 1500KHz, and the speed is 1200mm / s;
[0117] (11) The steps (9) and (10) are repeated to complete the preparation of the cathode functional layer, the thickness of the cathode functional layer is 20μm, the porosity is 50%, and a solid oxide fuel cell is obtained;
[0118] The prepared cell uses hydrogen as fuel, the power is 1.3W / cm 2 at 700℃, and the resistance is 0.35Ω / cm 2 .
[0119] Example 6
[0120] A method for manufacturing a solid oxide fuel cell, comprising the following steps:
[0121] (1) forming a porous metal support from a nickel-based superalloy metal support powder by continuous laser processing; the laser processing has a power of 350 W, a speed of 1500 mm / s, and a layer thickness of 80 μm for each powder laying in the continuous laser processing; the porous metal support has a thickness of 2 mm and a porosity of 50%;
[0122] (2) adding nano nickel oxide (NiO) and gadolinium-stabilized ceria (GDC) into anhydrous ethanol to obtain an anode aerosol solution (a solid phase content of 50 wt.%), the mass ratio of the nano nickel oxide (NiO) and the gadolinium-stabilized ceria (GDC) being 7:3; adding GDC into anhydrous ethanol to uniformly disperse and configure a 55 wt.% electrolyte aerosol solution; adding lanthanum strontium cobalt iron (LSCF) into anhydrous ethanol to uniformly disperse and configure a 50 wt.% cathode aerosol solution;
[0123] (3) using a large-capacity aerosol nozzle to spray the anode aerosol suspension onto the surface of the metal support;
[0124] (4) using ultrafast laser to perform laser sintering processing on the anode aerosol on the surface of the support, the laser power being 8 W, the repetition frequency being 1000 KHz, and the speed being 1500 mm / s;
[0125] (5) repeating steps (3) and (4) to complete the preparation of the anode functional layer, the layer thickness being 10 μm and the porosity being 30%;
[0126] (6) using a large-capacity aerosol nozzle to spray the electrolyte aerosol suspension onto the surface of the anode;
[0127] (7) using ultrafast laser to perform laser sintering processing on the electrolyte aerosol on the surface of the anode, the laser power being 8 W, the repetition frequency being 1500 KHz, and the speed being 800 mm / s;
[0128] (8) repeating steps (6) and (7) to complete the preparation of the electrolyte functional layer, the thickness of the electrolyte functional layer being 8 μm and the porosity being <0.1%;
[0129] (9) using a large-capacity aerosol nozzle to spray the cathode aerosol suspension onto the surface of the electrolyte functional layer;
[0130] (10) using ultrafast laser, laser sintering treatment is carried out on the cathode aerosol on the surface of the electrolyte functional layer, laser power 8W, repetition frequency 1000KHz, speed 1200mm / s;
[0131] (11) repeating step (9) and step (10), completing the preparation of the cathode functional layer, the thickness of the cathode functional layer is 10μm, the porosity is 40%, obtaining the solid oxide fuel cell;
[0132] The prepared cell uses hydrogen as fuel, the power is 0.9W / cm 2 at 700℃, the resistance is 0.5Ω / cm 2 .
[0133] The above examples are only the preferred embodiments of the present application, which are used for explaining the present application, but not limiting the present application, and the changes, replacements, modifications and the like made by the person skilled in the art without departing from the spirit and essence of the present application shall belong to the protection scope of the present application.
Claims
1. A method for manufacturing a solid oxide fuel cell, characterized in that, Includes the following steps: A porous metal support is prepared by continuous laser processing. An anode aerosol suspension is sprayed onto the porous metal support, and a first ultrafast laser sintering treatment is performed to obtain an anode functional layer. Then, an electrolyte aerosol is sprayed onto the anode functional layer, and a second ultrafast laser sintering treatment is performed to obtain an electrolyte functional layer. Finally, a cathode aerosol suspension is sprayed onto the electrolyte functional layer, and a third ultrafast laser sintering treatment is performed to obtain the solid oxide fuel cell.
2. The manufacturing method according to claim 1, characterized in that, The porous metal support has a thickness of 0.5–5 mm and a porosity of 20%–60%.
3. The manufacturing method according to claim 1, characterized in that, The preparation of the porous metal support includes the following steps: A porous metal support is obtained by continuous laser processing of metal powder; the power of the continuous laser processing is 100-400W, the scanning speed is 500-2000mm / s, and the thickness of the powder layer spread in each continuous laser processing is 20-100μm; the metal powder is at least one of stainless steel, nickel-based alloy, and cobalt-based alloy.
4. The manufacturing method according to claim 1, characterized in that, The preparation of the anolyte aerosol suspension includes the following steps: Nano-sized nickel oxide and gadolinium-stabilized cerium oxide are added to a solvent and dispersed evenly to prepare an anodic aerosol solution; the mass ratio of nano-sized nickel oxide to gadolinium-stabilized cerium oxide is 3:7 to 7:3; the solvent is deionized water, anhydrous ethanol, or a mixture of deionized water and anhydrous ethanol; the solid content of the anodic aerosol solution is 35 wt.% to 60 wt.%.
5. The manufacturing method according to claim 1, characterized in that, The preparation of the anode functional layer includes the following steps: An anode aerosol suspension is sprayed onto the porous metal support, followed by a first ultrafast laser sintering treatment. The process of spraying the anode aerosol suspension and undergoing the first ultrafast laser sintering treatment is repeated to obtain an anode functional layer with a thickness of 5–50 μm. The laser power of the first ultrafast laser sintering treatment is 2–20 W, the repetition frequency is 500–4000 kHz, and the speed is 100–5000 mm / s. The porosity of the anode functional layer is 20%–60%.
6. The manufacturing method according to claim 1, characterized in that, The preparation of the electrolyte aerosol solution includes the following steps: Gadolinium-stabilized cerium oxide is added to a solvent and dispersed evenly to prepare an electrolyte aerosol solution; the solvent is deionized water, anhydrous ethanol, or a mixture of deionized water and anhydrous ethanol; the solid content of the electrolyte aerosol solution is 35 wt.% to 60 wt.%.
7. The manufacturing method according to claim 1, characterized in that, The preparation of the electrolyte functional layer includes the following steps: An electrolyte aerosol solution is sprayed onto the anode functional layer, followed by a second ultrafast laser sintering treatment. This process of spraying the electrolyte aerosol suspension and performing the second laser sintering treatment is repeated to obtain the electrolyte functional layer, which has a thickness of 5–30 μm. The laser power of the second laser sintering treatment is 2–20 W, the repetition frequency is 100–4000 kHz, and the speed is 500–5000 mm / s. The porosity of the electrolyte functional layer is <0.3%.
8. The manufacturing method according to claim 1, characterized in that, The preparation of the cathode aerosol suspension includes the following steps: Lanthanum, strontium, cobalt, and iron are added to a solvent and dispersed evenly to obtain a cathode aerosol solution; the solvent is deionized water, anhydrous ethanol, or a mixture of deionized water and anhydrous ethanol; the solid content of the cathode aerosol solution is 35 wt.% to 60 wt.%.
9. The manufacturing method according to claim 1, characterized in that, The preparation of the cathode functional layer includes the following steps: A cathode aerosol suspension is sprayed onto the electrolyte functional layer, followed by a third ultrafast laser sintering process. This process is repeated to obtain the cathode functional layer, which has a thickness of 5–50 μm. The ultrafast laser power for the third ultrafast laser sintering process is 2 W–20 W, the repetition frequency is 100–4000 kHz, and the velocity is 500–5000 mm / s. The porosity of the cathode functional layer is 20%–60%.
10. A solid oxide fuel cell prepared by the manufacturing method according to any one of claims 1-9.